Chapter La narrazione come 'testimonianza'. L'evoluzione dell'ascolto tra filogenesi e ontogenesi dell'orecchio - CHIRICO', Donata (Moderna/Comparata, 2022)
The history of reflection on language is characterized by a singular ambiguity. For centuries, it has been carried on as if the existence of language and the cognitive-narrative capacities which derive from it were independently considered from the function that, on the other hand, founds and characterizes it, namely listening. We believe that the reason for this strangeness lies in the fact that there is no possible discourse on listening that does not lead to a discourse on the body, especially focusing on the body discourse of one's mother and her voice. On the contrary, this contribution aims to show that, in order to understand our history as talking and storytelling animals, it is important to reconstruct the specific journey that - in the course of both our phylogenesis and ontogenesis - the ear makes. It is, in fact, an organ already active in utero and on which, during our evolution, depends on both the emergence of the articulate voice and the bipedalism as well, as the posture par excellence of narration.